PENGUATAN PENDIDIKAN KARAKTER RELIGIUS SISWA MELALUI PEMBIASAAN DALAM BACA TULIS ALQUR’AN (BTQ) - Afnaz, Halimatuzzakiya; Dahlan, Zaini (Institut Syekh Abdul Halim Hasan Binjai, 2024)
Religious character education through reading and writing the Koran in the midst of today's changing world is important to maintain traditional values in religion. This study proposes a habituation approach in Reading and Writing the Qur'an (BTQ) as an effective method for strengthening students' morals and spirituality. Although this approach has been proven to have a positive impact, some weaknesses such as a lack of focus on the modern educational context still exist. This research aims to overcome these weaknesses and deepen understanding of the effectiveness of religious character education through BTQ. The focus is on exploring the extent to which BTQ education can strengthen students' religious character in the context of modern education. Its contribution is to provide deeper insight into the influence and effectiveness of religious character education through BTQ.